ANALYSIS OF CASH FLOW STATEMENTS TO ASSESS THE FINANCIAL PERFORMANCE PT. ADARO ENERGY Tbk - Mhd. Zulkifli Hasibuan; Mirwansyah Putra Ritonga; Dalyanto; Bayu Wulandari; Herdi (SEAN Institute, 2023)
A statement of cash flows that presents information about the inflows andoutflows and cash equivalents of an entity during a certain period. Thisstudy aims to help users predict future cash flow and find out how PT.Adaro Energy Tbk performs when measured using cash flow. Thisresearch method uses qualitative methods with descriptive analysis usingcash flows from operating activities, investing and financing. The resultsof this study indicates that the financial performance of PT. Adaro EnergyTbk is in bad shape for the period 2020-2019